Analysis on Plasma Treated Graphene Thin Film - Zailani, Ummi Shafiq'a Diyana; Mohamed Ali, Riyaz Ahmad (Evolution in Electrical and Electronic Engineering, 2020)
This paper presents a study on the graphene thin film with sample carbon nanotube (CNT) that has been treated with other gases such as Ar, CH3COOH, ethanol, and NH3. Spectroscopies study in this project includes X-ray photoelectron spectroscopy (XPS), Atomic Force Microscope (AFM), Field Emission Scanning Microscope (FESEM), and Energy Dispersive Spectroscopy (EDS). Besides, a study on the effect of graphene thin film treated by plasma to get the measurement and the criteria for each type of gases. The results on AFM did not provide a clear answer due to the noise on that sample but during FESEM and EDS experiment, there were another results that can make changes. This is because during the FE-SEM experiment, the magnificent resolution can show clearly that the surface topographical and the morphologies. In addition, results from EDS shows the types of material found in the sample.